If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2x + y) = 0 (2x * 6 + y * 6) = 0 (12x + 6y) = 0 Solving 12x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 12x + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 12x + 0 = 0 + -6y 12x = 0 + -6y Remove the zero: 12x = -6y Divide each side by '12'. x = -0.5y Simplifying x = -0.5y
| -3/2=2x^2 | | 2(x+5)=90 | | -3=1/2x-4 | | 2s^2-s-10=0 | | 1/4k=3(-1/4k+3) | | 1x-6=9 | | (.1x-33)+(.4x-40)=180 | | x=2x-132 | | (-3x+79)= | | 7st+4t(t+s+4)-9= | | x+7-4=-15 | | 300=-(420*600*1500)-(-1c*600*1500)-(1000*600*1500) | | -14+3x=11 | | 3u-8=-20 | | -10y=x+21 | | 4y-5+y+19=5y+20-2y | | 10=5+5y | | 2x=x-46*x-86 | | .1x-33+.4x-40=180 | | 1x-3=9 | | -6=5u+4 | | n+20=100 | | -6=1/2x-4 | | 7(5+6x)=203 | | 10-4(6-x)+5= | | -6=1/2x4 | | 6000=3x/2(2x) | | 2x+25+65=180 | | 8(y-6)=7(y+2) | | -21.8-g=9.5 | | 2x+3x-x= | | 2w+2=16 |